Indonesian Traditional Medicines: The Use Before And During The COVID-19 Pandemic At Online Pharmacy Networks In Indonesia - Happy Elda Murdiana; Mega Karina Putri; Dewi Rahmawati; Aloysia Yossy Kurniawati (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Many countries' use of traditional medicine during the COVID-19 pandemic aims to increase immunity and reduce symptoms caused by COVID-19. The use of traditional medicine, either alone or in combination with "western medicine" has become a concern for many countries to overcome the COVID-19 pandemic when drugs and vaccines are in the process of discovery and procurement. Methods: The main sales data obtained are included and excluded so that they can be compared, then coded according to the distribution permit classification, route of administration, country of origin, and usage claims. The analysis of the effect of the route of administration and country of origin is based on chi-square (chi-square count > chi-square table), which states that both have an effect. Results: The significance of the use of traditional medicines based on claims (p <0.05) before and during the COVID-19 pandemic was not significantly different. Conclusion: There is an effect of using Indonesian traditional medicine by classification of the route of use and country of origin. It is only a claim to help maintain liver health, which has a significant difference in the use of Indonesian traditional medicines before and during the COVID-19 pandemic, but the percentage of sales is decreasing.